NEW DIRECTIONS AND CHALLENGES FOR ODL: BUILDING A COLLABORATIVE BUSINESS APPROACH - Faridi, Mohammad Rishad; Ouseph, Shaju Nalkara (European Scientific Journal, ESJ, 2014)
Open and Distance Learning (ODL) has been undergoing incremental change over the past decade with the rapid flow of globalization and internationalization. At the surface level, the ODL platform seems to be volatile as greater challenges lie behind the pillars of open learning that ensures quality, flexibility and sustainability to its applicants. At the same time, it has become a promising alternative to the traditional classroom learning, helping university to move toward a vision of lifelong and on-demand learning. This paper aims at building a collaborative business model that can be adapted in an ODL setting keeping in mind the institution, students and stakeholders. It intends to identify effective management and efficient leadership who will be flagship in taking Open University into new heights. The objective is obvious as to make an analysis of anticipated variables of change, challenges, hindrances, facilitation, environment, and technology at ODL for the next decade. Accordingly, strategies are to be framed and effective policies are to be drawn through collaborative approach of leader and management-“an heuristic thought process”. It will also delineate the new trends in education management with special reference to ODL. This study is futuristic but the approach is empirical, with a vision of bringing competitive edge to education for all. As for methodology, the researchers sought opinions of various stakeholders in education and analyzed the priorities to be set in this area. The paradigm shift is from tutor to content and to learner where learning is taking place in a wider perspective with openness to creativity, novelty of ideas, active participation of the learner and stakeholder. ODL has to create a learning environment, coping with the challenges of technological developments involving digitalization and processing of information, emergence of new wave of economies, demographics and ageing population, changes in society and family structures. This necessitates fostering strong rapport between facilitator and learner with a robust support and encouragement of authentic/open leadership.